Viagem Interoceânica: uma epópeia acadêmica pela tríplice fronteira MAP - Guilherme Marinho Miranda (2018)
This thesis proposes a way to translate the space of the Interoceanic Highway, also known as the Pacific Highway, conceived as an integration hub – through Peru, Brazil and Bolivia – and lived by the different paths that cross the triple border “MAP” – Madre de Dios, Acre and Pando. An exercise of creative transposition from an abstract spatiality of a road into the terms of a differential spatial practice of a trip. This translation aims to dissolve the harsh and violent character of large-scale capitalist territorial planning through the affective density of a shared creative practice. Starting from a collective research trip, held in 2010, with the purpose of recording, in audio and video, the life histories and daily geographies of the road users, an operation of passage is built between a road, thought as an integration model, and the viable path of the lived differences. Thus, the research of a geographical context is joined by the research about a certain video graphic texture. The reader will find in this work some travel narratives, structured in 1102 fragments, gathered in 10 chants, preceded by a foreword and followed by a methodological argumentation. This structure is inspired by the deviation made by Gonçalo M. Tavares, through the book A Voyage to India (2010), a tiny epic text based on the classic epic text of Luís de Camões (The Lusiads, 1572). Here, these texts are displaced with the function of a critical and a recreational argumentation, in the form of an academic epic text. Thus, to the research of a contextual video-geographical texture comes, finally, the organization of a travel narrative. At the heart of this thesis, there is a methodological invention interested in pointing out and expanding the senses of the production of social space, according to Henri Lefebvre’s theory (1901-91). It happens through a video-geographic translation practice, made up of the intertwining of videos, words and sounds. A place opened to the inscription of the different positions of the bodies, with their singular and irreducible points of view, in the common plot of the research. A path of differences is expressed, therefore, through the perspectives of an academic epic translation gathered by Ivo C, a multiple character, and his Collective of researchers: Elvira C, Jandira R, Jean M, Luzia T and Osmar X. Dislocations, stops and itineraries that take us until the borders of an Amerindian Stream called Abyss – the last frontier of Western capitalist space.